1997
DOI: 10.1016/s0370-2693(96)01511-0
|View full text |Cite
|
Sign up to set email alerts
|

Double beta decay and the proton-neutron residual interaction

Abstract: The validity of the pn-QRPA and -RQRPA descriptions of double beta decay transition amplitudes is analyzed by using an exactly solvable model. It is shown that the collapse of the QRPA is physically meaningful and that it is associated with the appearance of a state with zero energy in the spectrum. It is shown that in the RQRPA this particular feature is not present and that this approach leads to finite but otherwise spurious results for the double beta decay transition amplitudes near the point of collapse.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…It has been shown that the choice of the spin-isospin terms of the Skyrme energy functional affects the calculated strength distribution and excitation energy of the GT resonance, i.e., the properties of the GTR are not entirely determined by the Landau-Migdal residual interaction [269]. In addition, the inclusion of particle-particle correlations in the QRPA residual interaction is important in calculations of the GT transition strength [294,295,296], β-decay rates [31,297,298] and double β-decay amplitudes [299,300]. The inclusion of proton-neutron pairing changes significantly the rates of the neutrinoless double β-decay, allowing for larger values of the expectation value of light neutrino masses [301].…”
Section: Gamow-teller Resonancesmentioning
confidence: 99%
“…It has been shown that the choice of the spin-isospin terms of the Skyrme energy functional affects the calculated strength distribution and excitation energy of the GT resonance, i.e., the properties of the GTR are not entirely determined by the Landau-Migdal residual interaction [269]. In addition, the inclusion of particle-particle correlations in the QRPA residual interaction is important in calculations of the GT transition strength [294,295,296], β-decay rates [31,297,298] and double β-decay amplitudes [299,300]. The inclusion of proton-neutron pairing changes significantly the rates of the neutrinoless double β-decay, allowing for larger values of the expectation value of light neutrino masses [301].…”
Section: Gamow-teller Resonancesmentioning
confidence: 99%
“…By comparing this expression with Eqs. (18), (19) and (20) we see that only the lowest intermediate state |4 ′ 3 > contributes to the sum rule within the considered approximation. We find again a combination of energies of involved states to be a function of pairing, particle-particle and particle-hole interactions:…”
Section: Fig 2: (Color Online) Matrix Element M 2νmentioning
confidence: 64%
“…The goal of this paper is to discuss the suppression mechanism of the double Fermi matrix element close to the point of restoration of isospin symmetry of the nuclear Hamiltonian in the context of residual nucleonnucleon interaction. For the sake of simplicity we consider a schematic Hamiltonian, describing the gross properties of the beta-decay processes in the simplest case of monopole Fermi transitions within the SO(5) model [16][17][18][19][20][21]. In order to find explicit dependence of M 2ν F on different parts of the nuclear Hamiltonian the perturbation theory is exploited.…”
Section: Introductionmentioning
confidence: 99%
“…This implies that states with explicit flavor will present un-physical states only for large number of bosons. If flavor (0,0) and spin 0 and 1 are considered, we have U(4Ω) ⊃ U(Ω)⊗U (4), which has as an upper limit the number Ω up to which no spurious states appear. Finally, for all pairs, i.e.…”
Section: (4ω) ⊃ U(2ω) ⊗ U(2) the Irrep Of U(4ω) Has To Be Antisymmetmentioning
confidence: 99%
“…An extended version of the Lipkin model was applied to the description of pion condensates in nuclei [2]. A variety of many body techniques have been tested with Lipkintype models [3,4]. In [3] some realistic, less schematic, nuclear interactions, suitable to describe various nuclear properties, were investigated in this way.…”
Section: Introductionmentioning
confidence: 99%